Expression and function of transcription factor cMyb during cranial neural crest development. - Betancur, P; Simões-Costa, M; Sauka-Spengler, T; Bronner, M (2014)
The transcription factor cMyb has well known functions in vertebrate hematopoiesis, but little was known about its distribution or function at early developmental stages. Here, we show that cMyb transcripts are present at the neural plate during gastrulation in chick embryos. cMyb expression then resolves to the cranial neural folds and is maintained in early migrating cranial neural crest cells during and after neurulation. Morpholino-mediated knock-down of cMyb reduces expression of Pax7 and Twist at the neural plate border, as well as reducing expression of neural crest specifier gene Slug/Snail2 and completely eliminating expression of Ets1. On the other hand, its loss results in abnormal maintenance of Zic1, but little or no effect on other neural crest specifier genes like FoxD3 or Sox9. These results place cMyb in a critical hierarchical position within the cranial neural crest cell gene regulatory network, likely directly inhibiting Zic1 and upstream of Ets1 and some, but not all, neural crest specifier genes.